Heme Interactions as Regulators of the Alternative Pathway Complement Responses and Implications for Heme-Associated Pathologies - Stefanos A. Tsiftsoglou (Current Issues in Molecular Biology, 2023)
Heme (Fe2+-protoporphyrin IX) is a pigment of life, and as a prosthetic group in several hemoproteins, it contributes to diverse critical cellular processes. While its intracellular levels are tightly regulated by networks of heme-binding proteins (HeBPs), labile heme can be hazardous through oxidative processes. In blood plasma, heme is scavenged by hemopexin (HPX), albumin and several other proteins, while it also interacts directly with complement components C1q, C3 and factor I. These direct interactions block the classical pathway (CP) and distort the alternative pathway (AP). Errors or flaws in heme metabolism, causing uncontrolled intracellular oxidative stress, can lead to several severe hematological disorders. Direct interactions of extracellular heme with alternative pathway complement components (APCCs) may be implicated molecularly in diverse conditions at sites of abnormal cell damage and vascular injury. In such disorders, a deregulated AP could be associated with the heme-mediated disruption of the physiological heparan sulphate–CFH coat of stressed cells and the induction of local hemostatic responses. Within this conceptual frame, a computational evaluation of HBMs (heme-binding motifs) aimed to determine how heme interacts with APCCs and whether these interactions are affected by genetic variation within putative HBMs. Combined computational analysis and database mining identified putative HBMs in all of the 16 APCCs examined, with 10 exhibiting disease-associated genetic (SNPs) and/or epigenetic variation (PTMs). Overall, this article indicates that among the pleiotropic roles of heme reviewed, the interactions of heme with APCCs could induce differential AP-mediated hemostasis-driven pathologies in certain individuals.